Strain‐Induced Structural Deformation Study of 2D MoxW(1‐x) S2. Issue 5 (28th January 2019) - Susarla, Sandhya; Manimunda, Praveena; Jaques, Ygor M.; Hachtel, Jordan A.; Idrobo, Juan C.; Asif, S. A. Syed; Galvão, Douglas S.; Tiwary, Chandra Sekhar; Ajayan, Pulickel M.
Abstract: The possibility of tuning properties and its potential applications in the fields of optoelectronics and/or flexible electronics, has increased the demand for 2D alloys in recent times. Understanding the mechanical performance of 2D materials under extreme conditions, such as strain, stress, and fracture is essential for the reliable electronic devices based on these structures. In this study, combined molecular dynamics (MD) simulations and in situ Raman spectroscopic techniques are used to study the mechanical performance of a 2D alloy system, Mo x W(1‐ x ) S2 . It is observed that W substitution in MoS2 causes solid‐solution strengthening and increase in the Young's modulus values. Higher W content decreases failure strain for MoS2 . Based on spatially resolved Raman spectroscopy and MD simulations results, a detailed model to explain failure mechanisms in Mo x W(1‐ x ) S2 alloys is proposed. Abstract : Mechanical properties of 2D alloys are an important property that has to be considered while designing flexible electronic devices. In this work, the mechanical properties such as fracture and strain of Mo x W(1‐ x ) S2 alloy are studied using in situ Raman spectroscopy and molecular dynamics simulations.